Efeito da sazonalidade e do tratamento térmico industrial no perfil de ácidos graxos do leite e resposta biológica de ratos com diferentes fontes lipídicas - Novack, Mariana Moura Ercolani (2014)
There is a great concern of consumers with health, food safety and nutritional value of foods that come with even more interest in sau-hum- ming, nutritious and great use food products. Aimed to evaluate the effect of seasonality and industrial heat treatment on fatty acids of milk and the biological response of rats on diets of different lipid sources submitted or not to physical activity profile. In assessing the effect of climate station and heat treatment on fatty acid profile of milk samples were collected (in natura, pasteurized and sterilized) for 11 consecutive months in the Rio Grande do Sul Dairy Industry. Samples were subjected to extraction lipids and after the determination of fatty acid profiles in gas chromatography, using patterns of fatty acids. The bioassay was conducted for a period of 52 days, we used 36 adult male Wistar rats, divided into 6 treatments of six animals each and were fed diet AIN- 93M, varying the source of lipids and regular physical activity: DCSA normolipídica control, with soybean oil and no physical activity; DCCA normolipídica control with soy oil and physical activity; DMSA fat with butter and no physical activity; DMCA fat with butter and physical activity; DGSA fat with hydrogenated vegetable fat and no physical activity; DGCA fat diet with hydrogenated vegetable fat and physical activity. We investigated the effect of treatments on feed intake, weight gain, feed conversion, feed efficiency ratio, weight, liver, kidneys, heart, epididymal fat digestibility of diets, blood parameters (total COL, HDL, TG, GLI , ALB, ALT, AST, urea, creatinine, IL-1, IL-6, IL-10, TNF-α, IFN-γ and PCRus) and the histology of the aortic arch. The sterilization of milk caused reduction of docosanoic fatty acids, conjugated linoleic acid (cis-9, trans-11) and eicosapentaenoic ratio PUFA: SFA. The seasonal variation caused in octadecatrienoic fatty acids, conjugated linoleic acid (cis- 9, trans-11), docosadienoic acid, and eicosapentaenoic ratio PUFA: SFA. The experimental diets interfere with the feed intake, weight gain, feed conversion ratio, feed efficiency coefficient, epididymal fat weight and total cholesterol blood parameters, alanine transaminase, aspartate transaminase, IL-1, IL-6 and IL-10. Physical activity influence on blood triglyceride, creatinine, IL-1, IL-6 and IL-10. The interaction between diet and physical activity was significant for TNF-α and INF-γ. From the results it can be concluded that the heat-treated milk (pasteurization and sterilization) produced in four seasons show variations in the fatty acid profile. The concomitant fat diet with regular physical activity promotes normal development and maintenance of experimental animals.